A study of teachers perception towards Pentaksiran Berasaskan Sekolah (PBS) in Timur Laut, Pulau Pinang / Nur Shazmin Zainudin and Nurul Atiqah Mohamad Aziz - Zainudin, Nur Shazmin; Mohamad Aziz, Nurul Atiqah (2014)
This chapter focuses the background of the study on the perceptions of primary schools teachers towards implementation of Pentaksiran Berasaskan Sekolah (PBS) in Timur Laut, Penang. Section 1.1 discuss the background of study, section 1.2 explains the problem statement and section 1.3 states the research questions. In addition, section 1.4 states the research objectives and 1.5 is on the information regarding the scope of study and lastly in section 1.6 explains the significant of study.